Efficacy of evidence-based medicine training for primary healthcare professionals: a non-randomized controlled trial - Fei, Jiaojiao (BMC Med Educ, 2018)
BACKGROUND: The impact of evidence-based medicine (EBM) training techniques in primary healthcare professionals remains to be determined. METHODS: A non-randomized controlled trial (NRCT) was performed aiming to assess the two methods of evidence-based medicine training for primary healthcare professionals by assessing evidence based practice (EBP) related knowledge (EBP-K), attitude (EBP-A), personal application (EBP-P), anticipated future use (EBP-F), and community management of hypertension. Participants were recruited and assigned to either an EBM training group that receiving a weekly face-to-face EBM training course, or an EBM self-instruction course for eight weeks. A validated instrument was applied to evaluate the four aspects of EBP. Additionally, community management of hypertension was assessed by comparing the the rate of detection, blood pressure control, standard management, grading management and patient satisfaction between 2015 and 2016 to measure training efficacy. The difference between the impact of these two interventions was assessed statistically. RESULTS: One hundred fifty-one participants (69 in the face-to-face EBM training group and 82 in the self-instruction group) were included. Compared to self-instruction, the face-to-face EBM training was associated with significantly improved EBP-Knowledge (26.14 ± 4.22 vs. 22.44 ± 4.47, P < 0.05), EBP-Personal application (22.52 ± 6.18 vs. 16.89 ± 5.99, P < 0.05), and EBP-Future use (44.04 ± 8.97 vs. 37.71 ± 8.39, P < 0.05). EBP-Attitude scores (10.89 ± 4.52 vs.14.93 ± 5.92, P < 0.000) were lower in the EBM training group. Stratified analyses showed that the results were consistent regardless of the participants’ gender, professional role (doctors & apothecaries or nurses), rank (junior or senior doctors & apothecaries), or specialty (Traditional Chinese or Western Medicine). Assessment of community hypertension management revealed that the rate of blood pressure control, standardized hypertension management and patient satisfaction was significantly better in group A than group B (1.14% vs.0.69, 2.85% vs.1.68 and 2.41% vs.0.84%). CONCLUSIONS: A face-to-face EBM training course improved primary healthcare professionals’ EBP knowledge, attitudes, personal application, and anticipated future use. Effective EBM training may improve the efficacy of primary health care services. TRIAL REGISTRATION: Non-Randomized Controlled Trial ChiCTR1800017498, August 1, 2018. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12909-018-1404-y) contains supplementary material, which is available to authorized users.